Audience Prototypes and Asymmetric Efficacy Beliefs - Rosenthal, Sonny (2017)
Prior research suggests that the third-person effect is related to media schemas, for example, that general audiences are vulnerable to influence. The current study evaluates whether the effect of media schemas depends on more specific audience schemas. Participants read descriptions of four “actors” in a 2 (gullible vs critical-minded) × 2 (heavy vs light Internet users) repeated measures experiment and rated how much the actors can resist the influence of media and how much they benefit from censorship. For comparison, participants rated themselves on the same dependent variables. Results show that gullible heavy Internet users are perceived to have the greatest self-regulatory inefficacy and benefit the most from censorship, while the outcome is opposite for critical-minded light Internet users. These patterns remains when evaluating self-other asymmetric efficacy beliefs, which the discussion situates in relation to motivational and cognitive processes underlying the third-person effect.